Authenticity and animal welfare: understanding and ameliorating the suffering of dairy cows and their calves - Teeple, Jennifer Elyse, author; Rollin, Bernard, advisor; Engle, Terry, committee member; Wailes, William, committee member (Colorado State University. Libraries, 2016)
As Bernard Rollin discusses throughout his body of work, animals have interests and unique teloi as well as the capacity to feel pain and suffer emotionally. I argue that we must confront the ways in which we contribute to the suffering of dairy cows and their calves in particular, for their lives constitute a paradigmatic denial of an animal’s telos. Martin Heidegger’s notion of everydayness and his concept of authenticity—and especially Charles B. Guignon’s interpretations of them—allow us to understand and come to terms with our own everyday contribution to the reprehensible practices surrounding dairy production. That is, Heidegger’s understanding of Being allows us to see that we are likely contributors to the perpetuation of dairy cow and calf suffering. The concept of authenticity also acts as a tool that allows us insight into describing and prescribing personal commitments that entail the amelioration of these animals’ suffering. The goal is to individually strive to improve animal welfare in the dairy industry, which entails taking responsibility for and altering our actions and choices; otherwise, to avoid doing so is culpable—a notion akin to Nancy Williams’s argument that we are affectively ignorant of our role in animal mistreatment. Finally, utilizing authenticity as a guide also allows us to look to history, idols, and exemplars for moral guidance.